Benoit, H. (2015). Platão e as temporalidades:: a questão metodológica. São Paulo, Annablume. - Souza, Eliane Christina (Revista Archai, 2015)
Benoit, H. (2015). Platão e as temporalidades: a questão metodológica. São Paulo, Annablume